2020
DOI: 10.1002/smll.201907016
|View full text |Cite
|
Sign up to set email alerts
|

Facilitate Gas Transport through Metal‐Organic Polyhedra Constructed Porous Liquid Membrane

Abstract: Type II porous liquids are demonstrated to be promise porous materials. However, the category of porous hosts is very limited. Here, a porous host metal–organic polyhedra (MOP‐18) is reported to construct type II porous liquids. MOP‐18 is dissolved into 15‐crown‐5 as an individual cage (5 nm). Both the molecular dynamics simulations and experimental gravimetric CO2 solubility test indicate that the inner cavity of MOP‐18 in porous liquids is unoccupied by 15‐crown‐5 and is accessible to CO2. Thus, the prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 27 publications
0
49
0
3
Order By: Relevance
“…Peng and co‐workers dissolved MOP‐18, which is decorated with 24 dodecoxy‐functional groups, in 15‐crown‐5. Both the solubility of and permeability toward carbon dioxide was shown to be higher in the porous liquid as compared to neat 15‐crown‐5 [235] . Given the synthetic versatility of both organic and metal–organic cages, we envision the expansion of this small library of porous liquids and their improvement for gas storage applications.…”
Section: Gas Storage In Solutions and Liquidsmentioning
confidence: 99%
“…Peng and co‐workers dissolved MOP‐18, which is decorated with 24 dodecoxy‐functional groups, in 15‐crown‐5. Both the solubility of and permeability toward carbon dioxide was shown to be higher in the porous liquid as compared to neat 15‐crown‐5 [235] . Given the synthetic versatility of both organic and metal–organic cages, we envision the expansion of this small library of porous liquids and their improvement for gas storage applications.…”
Section: Gas Storage In Solutions and Liquidsmentioning
confidence: 99%
“…This PL exhibits tailorable and enhanced CO 2 adsorption capacity. In another study, Peng et al [18] . prepared a homogeneous PL based on metal‐organic polyhedra (MOP‐18) and 15‐crown‐5 as the hindered solvent.…”
Section: Introductionmentioning
confidence: 99%
“…reported the construction of a type II porous liquid with porous host molecule of metal–organic polyhedra (MOP‐18) and a bulk solvent of 15‐crown‐5 (Figure 6). [27] The molecular size of the 15‐crown‐5 solvent was larger than the cage size of MOP‐18, so the 15‐crown‐5 in the porous liquid was excluded from the cavities of MOP‐18. Through the molecular dynamics simulation and experimentally gravimetric CO 2 solubility tests, it was confirmed that 15‐crown‐5 with MOP‐18 mass fraction of 5 wt % had permanent porosity.…”
Section: Type II Porous Liquidsmentioning
confidence: 99%
“… Schematic preparation process of porous liquid. Reproduced from ref., [27] Copyright (2020), with permission from Wiley‐VCH.…”
Section: Type II Porous Liquidsmentioning
confidence: 99%